Finnish Forest Sector Economic Outlook 2023–2024 : Executive Summary - Viitanen, Jari; Mutanen, Antti; Karvinen, Sari (Natural Resources Institute Finland (Luke), 2023)
After two peak years, the demand for Finnish forest industry products in key market areas has clearly weakened. The construction industry is plagued by inflation, high interest rates, and general uncertainty. The effects are transmitted to the Finnish forest industry's production, exports, felling volumes, and roundwood trade. In 2024, however, the demand for forest industry products is expected to pick up slightly. In the sawmilling industry, the economic out-look is weak, and the demand for sawnwood is expected to increase only at the end of next year when construction starts to recover. Finnish sawnwood production and export volumes will fall this year, and growth will remain marginal next year. Birch plywood production is limited by the availability of birch sawlogs. The demand for the pulp and paper industry products has also been sluggish, and production volumes in Finland have been shrinking since last year. Demand is expected to recover slightly during the next year. The profitability of the domestic forest industry will decrease significantly from previous years. The fellings of industrial roundwood will de-crease this year but will increase again to 63 million cubic metres in 2024. Increasing felling volumes improve employment in forestry. After the strong increase in the stumpage prices at the beginning of 2023, the prices have already turned down. In 2024, the stumpage prices of coniferous roundwood will decrease slightly compared to the current year. The use of wood chips and its plant price, as well as the production of pellets, will increase slightly.
Keywords: forest sector; forest products industry